Promoção do crescimento de jacarandá-mimoso (Jacaranda mimosifolia d. don) pelo emprego de Trichoderma spp. - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
The low volume of information related to the interaction of Trichoderma fungi with seeds and seedlings represents a limitation to forest production, and it is important to carry out studies focusing on its effect on plant germinability and formation. The aim of this study was to evaluate commercial products based on Trichoderma spp. promoting seedling growth and seedling development of Jacaranda mimosifolia D. Don. The evaluated commercial strains were: T. harzianum IBLF 006 WP, T. asperellum URM 5911, T. harzianum T-22 WG, T. harzianum ESALQ 1306 T. harzianum SIMBI T5. For the initial seedling growth evaluation, J. mimosifolia seeds were treated with 2 mL of Trichoderma spp. Suspension, placed on germinating paper sheets and stored in a germinator at 25ºC for 28 days. A treatment without inoculation with Trichoderma spp. was included as a witness. At 28 days after sowing (DAS) the following evaluations were performed: percentage germination (PG), root length (CR), shoot length (CPA), total length (CT), fresh root mass (MFR), shoot fresh mass (MPFA), total fresh mass (MFT), root dry mass (MSR), shoot dry mass (MSPA) and total dry mass (BIO). To evaluate the development of J. mimosifolia seedlings, the experiment was conducted in a greenhouse, where the soil of each pot (10 L) was treated with 8 mL of Trichoderma spp. (4.0 x 108 conidia / vessel). Then, J. mimosifolia seeds were sown and the evaluations performed at 120 DAS. The variables analyzed were those mentioned in the previous experiment plus: PG at 100 DAS, shoot height (ALT), stem diameter (DC), and Dickson quality index (IQD). Regarding initial seedling growth, the SIMBI T5, ESALQ1306 and T-22 WG strains stood out in relation to CR; while the ESALQ1306 and SIMBI T5 strains outperformed the CPA and CT. Regarding seedling development, the SIMBI T5 and ESALQ1306 strains presented higher values of ALT, CR, DC, MFT. Meanwhile, only the SIMBI T5 strain stood out for MSPA, MSR, BIO and IQD. The T. harzianum SIMBI T5 and T. harzianum ESALQ1306 strains promoted the initial development of J. mimosifolia seedlings via seed treatment. Regarding the development of seedlings of J. mimosifolia, the strain T. harzianum SIMBI T5 provided superior results in relation to the evaluations, in order to maximize the quality and yield of seedlings of the species.
Keywords: Produção florestal; Agente biopromotor; Desenvolvimento vegetal; Forest Production; Biopromotor agent; Plant development; CIENCIAS AGRARIAS